2020
DOI: 10.2215/cjn.11200919
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Recovery Associated with Kidney Failure due to Acute Kidney Injury

Abstract: Background and objectivesAKI requiring dialysis is a contributor to the growing burden of kidney failure, yet little is known about the frequency and patterns of recovery of AKI and its effect on outcomes in patients on incident dialysis.Design, setting, participants, & measurementsUsing the US Renal Data System, we evaluated a cohort of 1,045,540 patients on incident dialysis from January 1, 2005 to December 31, 2014, retrospectively. We examined the association of kidney failure due to AKI with the outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 32 publications
2
44
0
Order By: Relevance
“…Previous studies showed that early detection and treatment of AKI can help most patients recover renal function and reach a better clinical outcome [ 41 , 42 ]. Therefore, it is particularly important to identify the risk factors and prognostic factors for acute pancreatitis with acute renal injury in the early stage, so as to develop a predictive model to help clinicians take preventive intervention measures and avoid renal function damage [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that early detection and treatment of AKI can help most patients recover renal function and reach a better clinical outcome [ 41 , 42 ]. Therefore, it is particularly important to identify the risk factors and prognostic factors for acute pancreatitis with acute renal injury in the early stage, so as to develop a predictive model to help clinicians take preventive intervention measures and avoid renal function damage [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our ultimate goal is to advise nephrologists about the potential reversible predictors of outcomes to help improve the outcomes of these patients (e.g., improve specific laboratory parameters, optimize dialysis prescription and adequately manage reversible comorbidities). A recent study that evaluated a cohort of more than a million incident dialysis patients over 10 years (1/1/2005-12/31/2014) using the US Renal Data System (USRDS), of whom 1.1% were on dialysis secondary to AKI (n = 11,498), showed that women, non-whites (Blacks, Asians, Hispanics and Native Americans), and elderly patients are less likely to achieve kidney recovery compared to men, whites and young patients, respectively [12]. Similarly, Foley and colleagues showed a lower recovery rate of kidney function in women, Blacks, and Hispanics compared to men, Whites, and non-Hispanics, respectively [13].…”
Section: Introductionmentioning
confidence: 99%
“…Our study highlights diabetes as a risk factor for the development of AKD in patients with AKI, which is consistent with many other studies. [19][20][21] See et al 20 reported that diabetes was associated with poor long-term outcomes of AKI in a meta-analysis of cohort studies. In a Canadian population-based cohort study (n=190,714), Pannu et al found that participants with complicated diabetes were less likely to recover renal function.…”
Section: Main Risk Factors For Akd In Patients With Aki Diabetesmentioning
confidence: 99%